2007
DOI: 10.1002/jrs.1808
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectroscopy investigation using ab initio and density functional theory on flucytosine

Abstract: The FT Raman and FTIR spectra of flucytosine were recorded in the region 3500-100 cm −1 and 4000-400 cm −1 , respectively. The optimized geometry, wavenumber and intensity of the vibrational bands of flucytosine were obtained by ab initio and density functional theory (DFT) levels with complete relaxation in the potential energy surface using the 6-31G(d,p) and 6-311G(d,p) basis sets. A complete vibrational assignment aided by the theoretical harmonic frequency analysis is proposed. The harmonic vibrational wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…[113] In flucytosine, the fluoride substitution has a pronounced effect, upshifting the band by 38 cm −1 (Raman). [112] However, opposite shifts are seen in the NH 2 scissoring band upon substitution at different positions. There is coupling in this vibration to the phosphate group as well.…”
Section: Cytosinementioning
confidence: 89%
See 2 more Smart Citations
“…[113] In flucytosine, the fluoride substitution has a pronounced effect, upshifting the band by 38 cm −1 (Raman). [112] However, opposite shifts are seen in the NH 2 scissoring band upon substitution at different positions. There is coupling in this vibration to the phosphate group as well.…”
Section: Cytosinementioning
confidence: 89%
“…Seshadri et al [112] have reported a vibrational spectroscopic analysis of flucytosine for the first time, using HF and DFT methods with the 6-31G(d,p) and 6-311G(d,p) basis sets to characterize its IR and Raman spectra. The C 2 O carbonyl stretching mode has been predicted at 1682 cm −1 by B3LYP/6-311G(d,p).…”
Section: Flucytosinementioning
confidence: 99%
See 1 more Smart Citation
“…Literaturesurvey, points out that a complete quantum mechanical calculation for the selected title compound has not yet been reported so far. Quantum chemical calculations, and molecular modeling are playing a major role for drug design and research vibrational spectroscopy [ 8 , 9 , 10 , 11 ]. To find the structural information, functional groups, and other quantum level parameters, FT-IR, FT-Raman, NMR,UV-Visspectroscopyusing density functional theory (DFT) approaches are followed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, SERS was employed to determine the orientation of molecules on a metal surfaces. Such fundamental molecular structure studies were carried out for: 3,5-pyrazoledicarboxylic acid and its Ce(III) and Nd(III) complexes, 94 the bis(perfluoroethanesulfonyl)imide anion (BETI , 95 5-aminoorotic acid and its new lanthanide(III) complexes, 96 5-sulphosalicylic acid dihydrate, 97 3,5-dinitrosalicylic acid, 98 self-assembly complexes of bis(pyrrol-2-ylmethyleneamine) ligands linked by alkyl spacers with Cu(II) 99 thymine, uracil and their isotopomers, 100 the nonlinear optical chromophore p-bromoacetanilide, 101 1,3-disilabutane (SiH 3 CH 2 SiH 2 CH 3 , 102 dihaloheptasilanes X 2 Si[SiMe(SiMe 3 2 ] 2 with X = F, Cl, Br, 103 5-bromouracil, 104 uracilyl-pyridinium mesomeric betaine, 105 flucytosine, 106 the food additivesˇ-hydroxy-ˇ-methylobutanoic acid (HMB), L-carnitine, and N-methylglycocyamine (creatine), 107 clioquinol and its Cu(II) complex, 108 4-mercaptopyridine aqueous solution and 4-mercaptopyridine/Ag complex system. 109…”
Section: Vibrational Studies In Chemistry Combined Raman Infrared Smentioning
confidence: 99%